Checkpoint inhibition in hematologic malignancies - Tsumura, Aaron; Levis, Daniel; Tuscano, Joseph M. (Frontiers in Oncology, 2023)
Checkpoint inhibitor therapy has emerged as an effective therapeutic strategy for many types of malignancies, especially in solid tumors. Within the last two decades, numerous monoclonal antibody drugs targeting the CTLA-4 and PD-1/PD-L1 checkpoint pathways have seen FDA approval. Within hematologic malignancies, Hodgkin Lymphoma has seen the greatest clinical benefits thus far with more recent data showing efficacy in the front-line setting. As our understanding of checkpoint inhibition expands, using these pathways as a therapeutic target has shown some utility in the treatment of other hematologic malignancies as well, primarily in the relapsed/refractory settings. Checkpoint inhibition also appears to have a role as a synergistic agent to augment clinical responses to other forms of therapy such as hematopoietic stem cell transplant. Moreover, alternative checkpoint molecules that bypass the well-studied CTLA-4 and PD-1/PD-L1 pathways have emerged as exciting new therapeutic targets. Most excitingly is the use of anti-CD47 blockade in the treatment of high risk MDS and TP-53 mutated AML. Overall, there has been tremendous progress in understanding the benefits of checkpoint inhibition in hematologic malignancies, but further studies are needed in all areas to best utilize these agents. This is a review of the most recent developments and progress in Immune Checkpoint Inhibition in Hematologic Malignancies in the last decade.